(untitled) (Latakia University Journal -Medical Sciences Series, 2024)
Due to numerous studies demonstrating the positive impact of dietary fiber intake on human health, many dietary supplements incorporating these fibers have recently been marketed as a reliable source to fulfill the recommended daily need for optimal benefit. However, high consumer demand, difference in composition, and the need to ensure safety, make regulation and quality control of such supplement mandatory, thus determining the amount of these fibers in their preparations is considered the first stage in this regulation process. Dietary fibers are defined as edible starchy polymers that can’t be digested in human intestine, and are classified into water soluble and insoluble fibers. Crude fiber determination is one of the routine analytical methods used to measure the amount of fiber in food samples. Crude fiber is defined as the organic matter that remains after digesting the plant sample in a diluted sulfuric acid solution (1.25%) and then in a diluted potassium aqueous solution (1.25%). This research aimed to determine the amount of crude fiber in five products available in the local market that were declared to contain granules, psyllium seeds powder, or wheat bran powder, depending on the acid and alkaline digestion method. The percentages of crude fiber in these preparations 0.046 ± 0.0276, 75.867 ± 21.4715, 25.4833 ± 14.8368, 4.167 ± 0.384 and 1.07 ± 0.2961. The difference in the crude fiber content in these preparations, when compared with each other or with their counterparts that have been studied before, may be due to the difference in the plant variety used as raw materials and to the difference in manufacturing to manufacturing procedures during the production of these pharmaceutical preparations.This study recommends the need to determine the type and quantity of dietary fiber in commercial preparations containing it and add this information to their label.